E-Module: Innovation on Pancasila Student Profiles for First Grade of Elementary School in Pancasila Education Subjects - Ningsih, Ni Kadek Semartini Widya (Jurnal Media dan Teknologi Pendidikan, 2024)
The use of learning media at the elementary school level is still relatively monotonous, causing students to get bored in the learning process. Learning Pancasila education for grade I elementary school is very difficult to understand if it is not supported by appropriate learning media. This research aims to develop e-module learning media based on Pancasila student profiles for class I elementary school. This research uses the Dick and Carey development model. The data collection methods used were observation, interviews, questionnaires and tests. The subjects of this research were 4 experts and 68 students. The data obtained was analyzed using quantitative descriptive analysis techniques, qualitative descriptive analysis and inferential statistical analysis. The results of the expert assessment of content, design, media, language, individual trials and small group trials respectively obtained the qualifications very good (91.66%), very good (91.66%), good (88.33%), very good (93.33% ), very good (95.66%), and very good (95.00%). Based on the results of the media effectiveness test using the t-test technique, the Sig value was obtained. (2-tailed) is 0.000<0.05, so it can be stated that the e-module learning media based on Pancasila student profiles is effective for use in Pancasila subjects for class I elementary school. The innovation of e-modules based on Pancasila student profiles has implications for increasing the understanding of grade I elementary school students in the Pancasila subject and can overcome boredom due to monotonous learning.